2015
DOI: 10.1002/sdtp.10037
|View full text |Cite
|
Sign up to set email alerts
|

P‐11: Channel‐Etched CAAC‐OS FETs using Multi‐layer IGZO

Abstract: The improvement in the reliability of a channel-etched fieldeffect transistor (FET) using a buried channel effect was achieved by stacking In-Ga-Zn-O (IGZO) films with different compositions.In addition, a liquid crystal display panel using an IGZO multilayer c-axis-aligned crystal FET for a backplane was fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Our research group previously reported on back-channel-etched (BCE) and top-gate self-aligned (TGSA) field-effect transistors (FETs) with oxide semiconductor (OS) active layers [1][2][3][4][5][6]. OSbased FET (OSFET) technologies have recently been widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group previously reported on back-channel-etched (BCE) and top-gate self-aligned (TGSA) field-effect transistors (FETs) with oxide semiconductor (OS) active layers [1][2][3][4][5][6]. OSbased FET (OSFET) technologies have recently been widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…The authors previously developed OS FETs with back-channeletched (BCE) and top-gate self-aligned (TGSA) structures [1][2][3][4][5][6]. BCE OS FETs can be fabricated using fewer masks than those required for TGSA OS FETs.…”
Section: Introductionmentioning
confidence: 99%